Development of Electrical Discharge Machine Die Sinking Application Using Android Platform - Mohd Erfy Ismail; Masran S.H; Rahim M.B; Faizal A.N; Marian M.F (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The rapid development of Information Technology today has given a new impetus to the use of technology in education. It also affects the learning styles which changes into distance learning (d-learning) as well as mobile learning (m-learning). Its changes is consistent with the use of multimedia elements such as text, graphics and video in android application. This study aims to evaluate the developed Electrical Discharge Machine (EDM) Die Sinking applications using android platform in terms of design, development and function  based on teaching and learning theory. Random sampling technique was used to collect the data from 30 respondents in the year of 4 in Bachelor Degree of Technical Vocational (General Machining). The instruments to obtain information was in the form of questionnaire. Data were collected and analysed using SPSS (Statistical Package for the Social Sciences) version of 24. The study showed that this android applications meets the necessary criteria of content, presentation and interaction and it could help the students to understand the process of EDM Die Sinking